The Influence of Online Game Behaviors on the Emotional State and Executive Function of College Students in China - Zhao, Wei; Wei, Tao; Zhou, Ruidong; Wang, Yujing; Wang, Yan; Ren, Zixuan; Shao, Wenyi; Luo, Hanrun; Zhou, Yiding; Chen, Nuo; Lu, Qiao; Song, Xun; et al. (Frontiers in Psychiatry, 2021)
Background and Objective: Since the classification of gaming disorder (GD) by the World Health Organization (WHO) as “mental disorder caused by addictive behaviors,” there has been controversy regarding whether online game behaviors can lead to mental disorder. This study aims to clarify the correlation between the online game behaviors of college students and anxiety, depression, and executive function of college students in China, from a questionnaire-based investigation. Methods: Based on the whole class random sampling method, a questionnaire survey was conducted among college students in Northern Anhui, China from March 7 to March 27, 2020. The questionnaires included the Internet Game Addiction (IGA) Scale, Behavior Rating Inventory of Executive Function (Adult Version, BRIEF-A), Generalized Anxiety Disorder Scale (GAD-7) and Patient Health Questionnaire Scale (PHQ-9). Results: A total of 850 participants completed the survey, including 353 males (41.53%) and 497 females (58.47%). The primary age group was 18–27 years (91.53%), and the educational background was a bachelor's degree (94.7%). The study found that the online behavior of 17.76% of college students was online game behavior. This study did not identify any students who met the criteria for IGA, and 3% met the criteria for indulgent behavior. A dual role of online games was identified; moderate online game activities can improve the emotional state and executive function of college students, while excessive online game behaviors that may not reach the degree of addiction can also harm emotional state and executive function. Conclusions: This study suggests that although IGA has been regarded as a mental disease, online game behavior should be treated differently. Online game activities should not be entirely denied, but mental disorders caused by excessive gaming activities deserve attention. In particular, the emotional state and executive function of students with excessive online game behaviors should be monitored and intervened in advance to avoid game behaviors turning into indulgent behaviors or addiction. As a cognitive control process, executive function may play a key role in regulating IGA and emotional state.